2021
DOI: 10.1002/nop2.780
|View full text |Cite
|
Sign up to set email alerts
|

The nurses’ occupational stress components and outcomes, findings from an integrative review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 140 publications
0
18
0
2
Order By: Relevance
“…Moreover, 80% of the work is placed on the shoulders of nurses [11] . The occupational stress faced by nurses is likely to change due to massive changes in the environment, including the Coronavirus epidemic [12] . Health staff working in services such as the Emergency Department (ED) and Emergency Medical Services (EMS) are one of the vital assets of each country in case of critical cases such as the pandemic of COVID-19 [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 80% of the work is placed on the shoulders of nurses [11] . The occupational stress faced by nurses is likely to change due to massive changes in the environment, including the Coronavirus epidemic [12] . Health staff working in services such as the Emergency Department (ED) and Emergency Medical Services (EMS) are one of the vital assets of each country in case of critical cases such as the pandemic of COVID-19 [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Nurses’ stress has been investigated in many studies [ 45 ]. Researchers have shown that even in ordinary times (i.e., without a pandemic) nurses face many sources of stress resulting from their workload or patient-related issues, which affects their QoL [ 11 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such factors include too much work, job change, time pressure, heavy work duty, role change, too high requirements of job-aided hardware/devices for personal skills, irregular working hours, shifts, and work in poor natural and social environments, etc. Excessive work stress may lead to fatigue, anxiety, depression, reduced ability to work, and even burnout ( 13 15 ). The Information Management and Analysis, for example, reveals the highest proportion of overload-induced work stress, depending on its working style and method.…”
Section: Discussionmentioning
confidence: 99%